2009
DOI: 10.1016/j.bcp.2009.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid derivatised analogues of glucose-dependent insulinotropic polypeptide with improved antihyperglycaemic and insulinotropic properties

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Page 1 of 42A c c e p t e d M a n u s c r i p t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
5
35
0
Order By: Relevance
“…Food intake and body weight were similar to saline-treated control mice, consistent with other feeding studies in rodents (Irwin & Flatt 2009a, Kerr et al 2009, McIntosh et al 2009). As would be expected, a major benefit of twice-daily injection of GIP peptides centred on increased insulin section (Irwin & Flatt 2009a ]GIP(1-30) afforded partial protection of b-cell destruction in streptozotocintreated rats, resulting in greater glycaemic control and insulin responses (Widenmaier et al 2010).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Food intake and body weight were similar to saline-treated control mice, consistent with other feeding studies in rodents (Irwin & Flatt 2009a, Kerr et al 2009, McIntosh et al 2009). As would be expected, a major benefit of twice-daily injection of GIP peptides centred on increased insulin section (Irwin & Flatt 2009a ]GIP(1-30) afforded partial protection of b-cell destruction in streptozotocintreated rats, resulting in greater glycaemic control and insulin responses (Widenmaier et al 2010).…”
Section: Discussionsupporting
confidence: 88%
“…To this end, the results of the present study demonstrate similar beneficial effects of prolonged GIP receptor activation by both GIP-based molecules in high-fat fed mice. GIP(1-42) was confirmed as described previously (Kerr et al 2009;data not shown commencement of studies, the experimental animals were maintained on high-fat diet from 6 weeks of age for 140 days. Obesity, insulin resistance, and hyperglycaemia were clearly manifested compared to similarly aged mice maintained on normal laboratory diet as judged by body weight, plasma insulin, and glucose analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptides were characterised using matrix-assisted laser desorption ionisation time-of-flight (MALDI-TOF) mass spectrometry [23].…”
Section: Methodsmentioning
confidence: 99%
“…The specific CCK 1 and CCK 2 receptor antagonists, SR27897 and LY288513, were purchased from Tocris Biosciences (Avonmouth, UK). Peptides were characterised using matrix-assisted laser desorption ionisation time-of-flight (MALDI-TOF) mass spectrometry [17].…”
Section: Methodsmentioning
confidence: 99%